2024
DOI: 10.3390/ijms25084269
|View full text |Cite
|
Sign up to set email alerts
|

The Irony of Iron: The Element with Diverse Influence on Neurodegenerative Diseases

Seojin Lee,
Gabor G. Kovacs

Abstract: Iron accumulation in the brain is a common feature of many neurodegenerative diseases. Its involvement spans across the main proteinopathies involving tau, amyloid-beta, alpha-synuclein, and TDP-43. Accumulating evidence supports the contribution of iron in disease pathologies, but the delineation of its pathogenic role is yet challenged by the complex involvement of iron in multiple neurotoxicity mechanisms and evidence supporting a reciprocal influence between accumulation of iron and protein pathology. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 183 publications
(317 reference statements)
0
0
0
Order By: Relevance
“…It has been shown that moderate concentrations of zinc can improve seed germination, but high concentrations of zinc can inhibit plant growth [6]. Moderate amounts of iron can prevent or hinder protein pathology [7]. When manganese is deficient in animals, it interferes with normal growth rates [8].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that moderate concentrations of zinc can improve seed germination, but high concentrations of zinc can inhibit plant growth [6]. Moderate amounts of iron can prevent or hinder protein pathology [7]. When manganese is deficient in animals, it interferes with normal growth rates [8].…”
Section: Introductionmentioning
confidence: 99%